STUDI KEBERHASILAN PERTUMBUHAN TANAMAN KENARI (Canarium amboinensis) TAHUN KEDUA ASAL PROVENANS DESA NIKULUKAN SERAM DAN DESA KILANG AMBON PADA KEBUN BENIH DESA HATUSUA KECAMATAN KAIRATU - Manuputty, Ivana; Sahupala, Andjela; Talaohu, Moda (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to evaluate the second-year growth performance of kenari trees (Canarium amboinensis) from two different provenances Nikulukan Village (Seram Island) and Kilang Village (Ambon Island) planted at the Seed Orchard in Hatusua Village, Kairatu Subdistrict, West Seram Regency. A census method was applied to assess 800 kenari trees from both provenances. Parameters observed included plant height, diameter, survival rate, and environmental factors such as soil pH, air and soil humidity, rainfall, light intensity, and temperature. The results showed that the provenance from Nikulukan had a higher survival rate (95.25%) compared to Kilang (91.25%). A two-sample t-test revealed significant differences in height and diameter between the two provenances, with Nikulukan showing better growth performance. As environmental conditions were similar across the planting site, the differences in growth are presumed to be caused by the genetic adaptation of each provenance to the site.